2012
DOI: 10.1136/medethics-2011-100190
|View full text |Cite
|
Sign up to set email alerts
|

Is there no alternative? Conscientious objection by medical students

Abstract: Recent survey data gathered from British medical students reveal widespread acceptance of conscientious objection in medicine, despite the existence of strict policies in the UK that discourage conscientious refusals by students to aspects of their medical training. This disconnect demonstrates a pressing need to thoughtfully examine policies that allow conscience objections by medical students; as it so happens, the USA is one country that has examples of such policies. After presenting some background on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
13
0
4
Order By: Relevance
“…I will understand discrimination as different treatment based upon an arbitrary or irrelevant characteristic . Imagine a case in which male medical students of the Muslim faith conscientiously refuse to learn how to perform physical examinations on members of the opposite gender . Or imagine such physicians who were granted such an exemption then refusing to care for women on this basis.…”
Section: Developing the Reasonability Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…I will understand discrimination as different treatment based upon an arbitrary or irrelevant characteristic . Imagine a case in which male medical students of the Muslim faith conscientiously refuse to learn how to perform physical examinations on members of the opposite gender . Or imagine such physicians who were granted such an exemption then refusing to care for women on this basis.…”
Section: Developing the Reasonability Viewmentioning
confidence: 99%
“…17 Imagine a case in which male medical students of the Muslim faith conscientiously refuse to learn how to perform physical examinations on members of the opposite gender. 18 Or imagine such physicians who were granted such an exemption then refusing to care for women on this basis. Even though we can identify the tenets of belief system that support this putative conscientious objection, 19 it is imperative that we must be able to evaluate the reasonability of granting a conscientious objection on this basis.…”
Section: A Justified Conscientious Objection Must Not Be Based Upon Dmentioning
confidence: 99%
“…44 This indicates that conscientious objection remains a live debate for practitioners and students, particularly as the author held a view that conscientious objection is often discouraged among medical students. 45 Research among physicians in the United States has revealed that many approve of conscientious objection. 46,47,48 However, it is essential to consider that attitudes towards conscientious objection may be both country and profession specific, depending on cultural norms and professional regulation.…”
Section: Resultsmentioning
confidence: 99%
“…This reasoning suggests that honest exploration of the issues would help healthcare workers develop realistic approaches to deal with conscientious objections [56]. Although well-intentioned, the current culture of medicine does not necessarily always foster or condone open discussion [120].…”
Section: Broader Perspectives On Freedom Of Consciencementioning
confidence: 99%